2000
DOI: 10.1002/1529-0131(200005)43:5<1033::aid-anr11>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Chylomicron metabolism is markedly altered in systemic lupus erythematosus

Abstract: Objective. To verify the in vivo status of chylomi-cron metabolism in systemic lupus erythematosus (SLE) since there is a high incidence of atherosclerosis in this disease and chylomicrons may have an important role in atherogenesis. Methods. A chylomicron-like emulsion labeled with 14 C-cholesteryl esters and 3 H-triglycerides was injected intravenously into 10 female patients with inactive SLE and 10 healthy age-and sex-matched control subjects to determine the plasma kinetics of the emulsion lipids from con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
12

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(77 citation statements)
references
References 49 publications
2
63
0
12
Order By: Relevance
“…In SLE, prolonged steroid treatment seems to be the major cause in that it induces an atherogenic lipid profile, characterized by increased levels of very lowdensity lipoprotein and LDL and decreased levels of HDL, together with hypertension and diabetes (25). In the present study, HDL was reduced in SLE patients compared with controls, as has been reported previously (26). This reduction was quite significant for the HDL 2 subfraction.…”
Section: Discussionsupporting
confidence: 91%
“…In SLE, prolonged steroid treatment seems to be the major cause in that it induces an atherogenic lipid profile, characterized by increased levels of very lowdensity lipoprotein and LDL and decreased levels of HDL, together with hypertension and diabetes (25). In the present study, HDL was reduced in SLE patients compared with controls, as has been reported previously (26). This reduction was quite significant for the HDL 2 subfraction.…”
Section: Discussionsupporting
confidence: 91%
“…Premature atherosclerosis, as demonstrated by the presence of abnormal carotid intima-media thickness and flow-mediated dilation, has been reported both in adult and pediatric patients with SLE (6,(9)(10)(11)(12)(13)(14)(15)(16). Although both traditional and nontraditional factors are important in the development of premature atherosclerosis in patients with SLE, dyslipoproteinemia, which is present in 30-73% of adult patients with SLE, plays a role in the development of atherosclerosis (2,10,(17)(18)(19)(20)(21)(22)(23)(24). To date, there have been few comprehensive lipid studies in pediatric patients with SLE (5,6,16,(25)(26)(27).…”
mentioning
confidence: 99%
“…The classical pattern of dyslipoproteinemia in SLE is characterized by elevated levels of very-low-density lipoprotein cholesterol (VLDL), triglycerides and LDL and low levels of HDL (Borba, Bonfa et al 2000), although HDL qualitative abnormalities such as peroxidation have been also described, often in association with active disease. Peroxidised HDLs (piHDLs) are unable to reverse cholesterol transport which normally clears oxLDL from the subendothelial space promoting endothelial injury.…”
Section: Slementioning
confidence: 99%